Foundation engineering - Peck, Ralph B. (John Wiley and Sons, 1974)
The scope of the book has been enlarged to include discussions of foundations on rock, on swelling soils, on fill and on flexible earth-retaining structures such as braced and tieback walls and anchored bulkheads.